The effect of E-Digital services and the competence of health workers on the patient's interest in repeat visits mediated by the level of trust - Olivia Josephine; Hery Winoto Tj; Fushen Fushen (Enrichment : Journal of Management, 2023)
The purpose of this study was to determine the effect of E-Digital services and the competence of health workers on patients' interest in repeat visits mediated by the level of trust. The population in this study were patients who had made repeated visits to the Pratama Medizen Clinic and were processed using Structural Equation Model (SEM) analysis with PLS SEM software. Based on the results of the study, empirical facts were obtained in the form of: 1) There was a significant positive effect of the e-Digital Service variable on Interest in Repeat Visits; 2) There is a positive effect of the Competency of Medical Personnel variable on Interest in Repeat Visits; 3) There is a significant positive effect of the patient's trust variable on interest in repeat visits; 4) There is a positive effect of the e-Digital Service variable on Patient Trust; 5) There is a positive influence of the Competence of Medical Personnel variable on Patient Confidence; 6) Patient Trust has a significant positive mediating effect on e-Digital Services on Interest in Repeat Visits; 7) Patient Trust has a significant positive mediating effect on the Competence of Medical Personnel variable on Interest in Repeat Visits. The implications of this study can use other variables that influence interest in repeat visits to complement previous studies. Conducted on different companies or other institutions so that it will be a more comprehensive research. Using different respondents and adding the number of samples as well as completing the research theoretical basis in more detail so that the resulting analysis results are more accurate.